PENGARUH KOMPETENSI, ETIKA AUDITOR, PENGALAMAN AUDITOR, FEE AUDIT DAN AUDIT TENURE TERHADAP KUALITAS AUDIT PADA KANTOR AKUNTAN PUBLIK DI BALI - Ni Luh Devi Yuniantari; Luh Komang Merawati; Ida Ayu Ratih Manuari (Journal Research of Accounting, 2023)
The existence of the public accounting profession will gain the trust of the public if the auditors produce quality audits. Audit quality is influenced by many factors including competence, auditor ethics, auditor experience, audit fees and audit tenure. This study aims to analyze and explain the effect of competence, auditor ethics, auditor experience, audit fees and audit tenure on audit quality. The study population comprised all auditors employed at public accounting firms in Bali. Purposive sampling was employed, yielding 88 respondents. Data collection involved validated and reliable questionnaire. The data analysis method employed in this investigation was multiple linear regression analysis. The findings reveal that auditor ethics and experience positively influence audit quality, while competence, audit fees, and audit tenure exhibit no significant impact on audit quality